Electromagnetic wave shielding sheet, shielded wafer, semiconductor device and its manufacturing method
A specialized electromagnetic shielding sheet with controlled properties is applied to semiconductor wafers before singulation, addressing the need for high-density packaging by ensuring effective coverage and adhesion, thus enhancing production efficiency and reducing interference.
Patent Information
- Application Number
- JP2024164422
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-09-20
AI Technical Summary
There is a demand for high-density packaging of smaller and lighter semiconductor packages, requiring an electromagnetic shielding solution that can cover semiconductor wafers before singulation and after dicing, enhancing versatility and economy in mass production.
A highly reliable electromagnetic shielding sheet with specific properties, including a binder component and conductive filler, is applied to semiconductor wafers before singulation, forming a shield cover layer that adheres well and covers the wafer's entire surface, including half-cut grooves, with controlled elongation and Young's modulus, and resistance values.
The solution provides excellent coverage and adhesion, reducing electromagnetic interference, and facilitates efficient production of shielded semiconductor devices with minimal peeling and warping, suitable for various applications.
Smart Images

Figure 0007616470000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an electromagnetic wave shielding sheet, a shielded wafer, a semiconductor device, and a method for manufacturing the same. [Background technology]
[0002] In order to prevent malfunctions of semiconductor components integrated inside electronic devices such as mobile terminals, technology is needed to block electromagnetic noise generated by the semiconductor components as well as electromagnetic noise from the outside. Patent Document 1 discloses a method for manufacturing a mounting structure including a step of preparing a mounting member having a first circuit member and a plurality of second circuit members mounted on the mounting member, a step of forming a first hardened layer that covers the mounting member, and a step of forming a functional layer such as a shield cover layer on the first hardened layer by a vapor phase method and / or a plating method, etc. Patent Document 2 discloses an electromagnetic wave shielding sealing material with a supporting substrate that includes a supporting substrate having electromagnetic wave shielding properties and a sealing material laminated on the supporting substrate. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2019 / 117259 [Patent Document 2] JP 2016-092275 A Summary of the Invention [Problem to be solved by the invention]
[0004] In response to the trend towards lighter, thinner, shorter, and smaller electronic devices, there is a demand for high-density packaging that will also reduce the size and weight of semiconductor packages. For this reason, attention is being paid to wafer-level chip-size packaging (WL-CSP) technology, which does not use internal wiring with bonding wires, but forms external terminals and sealing resin before the wafer is diced, and packages semiconductor elements formed on the wafer. If it were possible to provide an electromagnetic shielding sheet that can cover such wafers in one go and also cover the sides of the semiconductor devices after dicing, it would be extremely advantageous in terms of versatility, economy, and mass production.
[0005] The present disclosure has been made in consideration of the above background, and aims to provide a highly reliable electromagnetic wave shielding sheet that can collectively cover a semiconductor wafer before it is diced and has excellent covering properties, as well as a shielded wafer, a semiconductor device, and a method for manufacturing the same that are formed using the electromagnetic wave shielding sheet. [Means for solving the problem]
[0006] As a result of extensive investigations, the present inventors have found that the problems of the present disclosure can be solved in the following aspect, and have thus completed the present disclosure. [1]: An electromagnetic wave shielding sheet for collectively covering at least one of the main surfaces of a semiconductor wafer before being singulated, the semiconductor wafer having half-cut grooves formed in a lattice pattern and element formation regions partitioned by the half-cut grooves and arranged in a matrix pattern, The electromagnetic wave shielding sheet has at least a shielding film containing a binder component and a conductive filler (F), The electromagnetic wave shielding sheet has an elongation rate of 100 to 1500% at 100°C, The electromagnetic wave shielding sheet, wherein the electromagnetic wave shielding sheet is cured after being treated at 180° C. for 2 hours and has a Young's modulus at 100° C. of 100 to 1000 MPa. [2]: The electromagnetic wave shielding sheet according to [1], wherein the electromagnetic wave shielding sheet is thermocompression-bonded to the entire main surface of a silicon bare wafer at 120°C and 5 MPa for 3 minutes, and then treated at 180°C for 2 hours. After that, a shield cover layer derived from the electromagnetic wave shielding sheet is subjected to a pressure cooker test based on JIS K5600-5-6, and then the peeling rate in an adhesion test is less than 15%. [3]: The electromagnetic wave shielding sheet according to [1] or [2], wherein the binder component contains a curable compound (C) having a weight-average molecular weight of 5,000 or less and a high molecular weight resin (P) having a weight-average molecular weight of 10,000 or more. [4]: The electromagnetic shielding sheet according to any one of [1] to [3], wherein the content of the conductive filler (F) is 45 to 85 mass %. [5]: Average specific surface area [m 2 / g] and the content [g] of the conductive filler (F) per 100 parts by mass of the binder component is 50 to 1200 [m 2 The electromagnetic wave shielding sheet according to any one of [1] to [4], wherein [6]: The electromagnetic wave shielding sheet according to any one of [1] to [5], wherein the curable compound (C) contains an epoxy group-containing compound (E) having a weight average molecular weight of 5,000 or less, the epoxy equivalent of the epoxy group-containing compound (E) is 110 to 1000 g / eq, and the epoxy group-containing compound (E) is contained in an amount of 10 to 80 parts by mass per 100 parts by mass of the high molecular weight resin (P). [7]: The electromagnetic wave shielding sheet according to any one of [1] to [6], wherein the electromagnetic wave shielding sheet is thermocompression-bonded to the entire main surface of a 12-inch silicon bare wafer having half-cut grooves, each 200 μm wide and 200 μm deep, formed in a lattice pattern at intervals of 4,000 μm, at 120° C. and 5 MPa for 3 minutes, and then treated at 180° C. for 2 hours to form a shield cover layer derived from the electromagnetic wave shielding sheet, and the resistance between the shield cover layer covering adjacent convex portions via the half-cut grooves is 5 to 300 mΩ. [8]: A shielded wafer having a shield cover layer formed on at least one main surface of a semiconductor wafer before singulation using the electromagnetic wave shield sheet according to any one of [1] to [7]. [9]: A semiconductor device obtained by dividing the shielded wafer according to [8] into individual element formation region units.
[10] : A step of forming half-cut grooves in a semiconductor wafer before being singulated, the semiconductor wafer having element formation regions formed in a matrix along scribe lines; a step of placing the electromagnetic wave shielding sheet according to any one of [1] to [7] above the semiconductor wafer; a step of thermocompression bonding the electromagnetic wave shielding sheet to the semiconductor wafer; a step of obtaining a shielding cover layer by heating and curing the electromagnetic wave shielding sheet; and dividing the semiconductor device into individual element formation region units. Effect of the Invention
[0007] The present disclosure has the excellent effect of providing a highly reliable electromagnetic wave shielding sheet that can collectively cover a semiconductor wafer before it is diced and has excellent coverage, as well as a shielded wafer, a semiconductor device, and a manufacturing method thereof that are formed using the electromagnetic wave shielding sheet. [Brief description of the drawings]
[0008] [Figure 1] FIG. 2 is a schematic explanatory view showing an example of a wafer according to the embodiment. [Diagram 2] FIG. 2 is a cross-sectional view taken along line II-II of FIG. [Diagram 3] A partially enlarged view of Figure 2. [Figure 4] FIG. 11 is a schematic cross-sectional view showing an example of a shielded wafer according to Modification 1. [Diagram 5] FIG. 11 is a schematic cross-sectional view showing an example of a shielded wafer according to Modification 2. [Figure 6] FIG. 11 is a schematic cross-sectional view showing an example of a shielded wafer according to Modification 3. [Figure 7] FIG. 2 is a side view showing an example of an electromagnetic wave shielding sheet according to an embodiment. [Figure 8] FIG. 11 is a side view showing an example of an electromagnetic wave shielding sheet according to a modified example. [Figure 9] 1 is a schematic cross-sectional view showing an example of a main part of a semiconductor device according to an embodiment; [Figure 10] FIG. 11 is a schematic cross-sectional view showing an example of a main part of a semiconductor device according to a modified example. [Figure 11] 5A to 5C are schematic explanatory views showing an example of a manufacturing process of the semiconductor device according to the embodiment. [Figure 12] 5A to 5C are schematic explanatory views showing an example of a manufacturing process of the semiconductor device according to the embodiment. [Figure 13] 5A to 5C are schematic explanatory views showing an example of a manufacturing process of the semiconductor device according to the embodiment. [Figure 14] 5A to 5C are schematic explanatory views showing an example of a manufacturing process of the semiconductor device according to the embodiment. [Figure 15] 5A to 5C are schematic explanatory views showing an example of a manufacturing process of the semiconductor device according to the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present disclosure will be described in detail below. Other embodiments are also included in the scope of the present disclosure as long as they are consistent with the gist of the present disclosure. In this specification, a numerical range specified using "~" includes the values written before and after the numerical value. Unless otherwise noted, each of the various components in this specification may be used independently, either alone or in combination of two or more types. The numerical values described in this specification refer to values obtained by the methods described in the Examples below.
[0010] 1. Shielded wafer The shielded wafer of the present disclosure is a wafer having a shield cover layer (hereinafter also referred to as an SC layer) formed by covering at least one main surface of a semiconductor wafer before singulation with an electromagnetic shielding sheet (hereinafter also referred to as an ES sheet) of the present disclosure. The ES sheet is a sheet for covering a semiconductor wafer (hereinafter also simply referred to as a wafer) at once, and has at least a shielding film containing a binder component and a conductive filler (F). In this specification, the conductive filler (F) (hereinafter also simply referred to as a filler (F)) refers to a filler that reflects electromagnetic waves. The binder component is a matrix component that forms a layer, and examples thereof include resins, curable compounds that can form a crosslinked structure by curing treatment, monomers, and oligomers.
[0011] The ES sheet has an elongation rate of 100 to 1500% at 100°C. The cured sheet obtained by treating the ES sheet at 180°C for 2 hours has a Young's modulus of 100 to 1000 MPa at 100°C. The cured sheet referred to here is the ES sheet that is cured without being bonded to an adherend. The above-mentioned condition of treating at 180°C for 2 hours is a curing condition for specifying the characteristics of the ES sheet. In other words, the curing condition for covering a wafer with the ES sheet to obtain a shield cover layer is not limited to the condition of treating at 180°C for 2 hours. The elongation rate is calculated by "100 x (length after elongation - original length) / (original length)".
[0012] The object of coating with this ES sheet is a wafer before the singulation process. Specific examples include a wafer on which a wafer level chip size package (WL-CSP) is formed before singulation, a wafer on which a semiconductor element is formed before singulation, a wafer on which a multilayer wiring structure or the like is formed before singulation, a bare wafer, and a wafer on which a thermal oxide film is formed by high-temperature treatment of a bare wafer.
[0013] The surface to be coated by the ES sheet may be the element formation area surface of the wafer or the back side thereof, and may be either single-sided or double-sided. The ES sheet can form an SC layer all at once on the wafer before it is diced, resulting in excellent productivity. The ES sheet has excellent conformability to uneven shapes, making it suitable for collectively coating wafers having half-cut grooves formed in a lattice shape and element formation areas partitioned by the half-cut grooves and arranged in a matrix. By collectively coating the half-cut grooves as well, an SC layer can be easily formed on the side of the semiconductor device after dicing.
[0014] The area to be covered by the ES sheet may be the entire surface of the wafer or a part of the wafer. For example, the ES sheet may be applied to cover approximately 80% of the area of the main surface of the wafer at once. The bare wafer is a wafer before processing, and examples of the bare wafer include semiconductor substrates such as single crystal silicon, gallium arsenide, and indium phosphide. The wafer diameter and thickness are arbitrary. The bare wafer diameter is, for example, 100 mm, 150 mm, 200 mm, 300 mm, and 450 mm. The bare wafer (semiconductor substrate) thickness is, for example, approximately 400 to 1000 μm.
[0015] FIG. 1 shows a schematic diagram of an example of the shielded wafer of this embodiment, and FIG. 2 shows a cross-sectional view of the II-II cut portion of FIG. 1. As shown in FIG. 2, the shielded wafer 101 has a multilayer wiring structure 14 formed on a semiconductor element forming wafer 1, and the semiconductor element forming wafer 1 and the multilayer wiring structure 14 are covered with an SC layer 2. By having the SC layer 2, electromagnetic waves generated from the semiconductor element of the semiconductor element forming wafer 1 or the wiring of the multilayer wiring structure 14 can be shielded. In addition, electromagnetic waves from the outside can be shielded to prevent malfunction of the semiconductor device. The thickness of the SC layer can be appropriately designed depending on the application. The thickness of the SC layer is usually about 1 to 300 μm. The lower limit of the thickness is more preferably 3 μm, more preferably 5 μm, and even more preferably 10 μm. The upper limit of the thickness is more preferably 150 μm, more preferably 100 μm, and even more preferably 50 μm.
[0016] 1 and 2, the shield processed wafer 101 has a semiconductor element forming wafer 1, half-cut grooves 11 formed in a lattice shape in the X-axis and Y-axis directions of the semiconductor element forming wafer 1, element forming regions 12 partitioned by the half-cut grooves 11 and arranged in a matrix shape, and an SC layer 2. The element forming regions 12 are regions that will be made into chips in a singulation process described later. As shown in FIG. 1, the semiconductor element forming wafer 1 has notches 13 serving as crystal orientation indicators provided at its end.
[0017] The half-cut grooves 11 are grooves formed from the upper surface of the multilayer wiring structure 14 to the middle of the thickness direction of the semiconductor substrate of the semiconductor element forming wafer 1, and are formed along scribe lines 17 formed in a lattice shape along the X-axis and Y-axis. The width of the half-cut grooves 11 is, for example, 20 to 500 μm. The depth of the half-cut grooves 11 from the upper surface of the semiconductor element forming wafer 1 is, for example, 40 to 600 μm. The half-cut grooves 11 can be formed by known methods such as mechanical cutting using a rotating blade or laser grooving. The half-cut grooves also include a mode in which the grooves do not reach the semiconductor element forming wafer 1 and are formed only in the multilayer wiring structure 14.
[0018] 3, the multilayer wiring structure 14 includes a first insulating film 15a, a second insulating film 15b, and a third insulating film 15c laminated in this order, with a plurality of metal patterns such as wiring 16 formed on each layer. A surface protection film (not shown) or the like may be further formed on the upper layer of the multilayer wiring structure 14.
[0019] The SC layer is composed of a single layer or multiple layers, as described later, and has at least a shield layer. The SC layer 2 shown in FIG. 2 is composed of a shield layer 20. The shield layer is a layer in which a shield film containing a binder component and a conductive filler (F) is cured. The shield layer 20 may be a single layer or multiple layers. The SC layer may also be a laminate of a shield layer 20a and a non-shield layer 21 as shown in FIG. 4. The non-shield layer 21 may be disposed on the side of the multilayer wiring structure 14 as in the example of FIG. 4, or vice versa. Examples of the non-shield layer 21 include a light-shielding layer, a hard coat layer, an insulating layer, a heat-conducting layer, and a protective layer. The non-shield layer 21 may be a single layer or multiple layers of the same or different types.
[0020] The shielded wafer may be a wafer on which a wafer level chip size package (WL-CSP) is formed. FIG. 5 shows a schematic cross-sectional view of an example of a WL-CSP shielded wafer before singulation. As shown in the figure, the shielded wafer 101b has electrode pads 4, a surface protective film 5, electrode posts 6, a sealing resin 7, an SC layer 2, etc. on the upper surface of the semiconductor element forming wafer 1. By singulating the shielded wafer 101b, a semiconductor device whose sides are covered with the SC layer 2 is obtained. The obtained semiconductor device is mounted on a printed circuit board (not shown) or the like via solder balls (not shown) placed on the electrode posts 6.
[0021] 6 shows a schematic cross-sectional view of another example of a shield processed wafer on which a WL-CSP is formed. The shield processed wafer 101c has a multilayer wiring structure 14 on the upper surface of the semiconductor element formed wafer 1, and this multilayer wiring structure is sealed with a sealing resin 7. The semiconductor element formed wafer 1 and the sealing resin 7 are covered with an SC layer 2. By singulating the shield processed wafer 101c, semiconductor devices each having an upper surface and sides covered with the SC layer 2 are obtained.
[0022] 2.Electromagnetic wave shielding sheet FIG. 7 shows a schematic side view of an example of the ES sheet of this embodiment. The ES sheet 3 shown in the figure is made of a shielding film 30. The shielding film 30 may be a single layer or a multi-layer. The ES sheet may be an ES sheet 3a in which one or more shielding films 30 and one or more non-shielding films 31 are laminated, as shown in FIG. 8. The shielding film 30 is coated to become the shielding layer 20. The non-shielding film 31 is coated to become the non-shielding layer 21. Examples of the non-shielding film 31 include an insulating film, a heat-conducting film, a light-shielding film, and a hard coat film. When the ES sheet has a non-shielding film, it is preferable to ensure a sufficient thickness of the shielding film from the viewpoint of fully exerting the shielding effect. From this viewpoint, it is preferable that 50 to 90% of the thickness of the ES sheet is the shielding film, and more preferably 55 to 80%.
[0023] The elongation of the ES sheet at 100°C is 100-1500%. In addition, the Young's modulus of the cured sheet after treating the ES sheet at 180°C for 2 hours is 100-1000MPa at 100°C. The ES sheet, which combines these features, can improve conformability to uneven shapes when pressing the ES sheet together. It can also suppress cracking of the wafer and warping of the wafer after curing. Furthermore, it can suppress peeling of the SC layer from the adherend and effectively suppress tearing in recesses such as half-cut grooves.
[0024] The lower limit of the elongation rate is more preferably 150%, and even more preferably 200%. The upper limit of the elongation rate is more preferably 1200%, and even more preferably 1000%. The lower limit of the Young's modulus is preferably 150 MPa, more preferably 200 MPa, and even more preferably 300 MPa. The upper limit of the Young's modulus is preferably 800 MPa, and more preferably 600 MPa. When the ES sheet is made of a laminate of multiple films, it is not necessary for each film to satisfy the above conditions, and it is sufficient that the elongation rate and the Young's modulus are satisfied in the present ES sheet.
[0025] The thickness of the ES sheet can be appropriately designed depending on the application. The thickness of the ES sheet is usually about 2 to 500 μm. The lower limit of the thickness is more preferably 5 μm, even more preferably 8 μm, and even more preferably 12 μm. The upper limit of the thickness is more preferably 300 μm, even more preferably 200 μm, and even more preferably 100 μm. The ES sheet is suitable for a coating layer that is coated so as to follow the uneven shape as shown in FIG. 2, but may also be used as an embedding layer in which the ES sheet is embedded (filled) in recesses.
[0026] From the viewpoint of enhancing reliability, the present ES sheet is thermocompression-bonded to the entire main surface of a silicon bare wafer at 120°C and 5 MPa for 3 minutes, and then treated at 180°C for 2 hours. After performing a pressure cooker test based on JIS K5600-5-6, the electromagnetic wave shielding layer derived from the electromagnetic wave shielding sheet preferably has a peeling rate of less than 15%, more preferably less than 10%, and even more preferably less than 5% in an adhesion test.
[0027] The ES sheet is thermocompressed at 120°C and 5 MPa for 3 minutes on the entire main surface of a 12-inch silicon bare wafer on which half-cut grooves, each 200 μm wide and 200 μm deep, are formed in a grid pattern at intervals of 4000 μm, and the resulting SC layer is cured at 180°C for 2 hours. The resistance between the center of the SC layer covering a convex portion (in the example of FIG. 6, the convex portion in which the multilayer wiring structure portion 14 is sealed with the sealing resin 7) and the center of the convex portion adjacent to the convex portion across the half-cut groove (between the shield cover layers on the adjacent convex portions) is preferably 5 to 300 mΩ. The upper limit of the resistance is more preferably 150 mΩ, more preferably 100 mΩ, and even more preferably 50 mΩ. The lower limit of the resistance is more preferably 7 mΩ, more preferably 10 mΩ, and even more preferably 15 mΩ.
[0028] As described above, the shielding film 30 contains a binder component and a conductive filler (F). The shielding film 30 becomes the shielding layer 20, which is a cured product, by a thermal curing treatment. The thickness of the shielding film 30 is, for example, 5 to 100 μm. From the viewpoint of achieving both suitability for processing into a wafer and electromagnetic wave shielding properties, the lower limit of the thickness of the shielding film 30 is preferably 7 μm, more preferably 10 μm, and even more preferably 20 μm. On the other hand, the upper limit of the thickness of the shielding film is preferably 90 μm, more preferably 75 μm, and even more preferably 50 μm.
[0029] 2-1.Shielding film The binder component of the shielding film 30 plays a role in holding the filler (F) in the film and forming the film. The binder component includes a component that forms a cross-linked structure by a curing treatment.
[0030] A suitable example of the binder component is a combination of a high molecular weight resin (P) with a weight average molecular weight (Mw) of 10,000 or more and a curable compound (C) with an Mw of 5,000 or less. By combining a high molecular weight resin (P) with an Mw of 10,000 or more and a curable compound (C) with an Mw of 5000 or less, the ES sheet can have excellent film-forming properties while also having excellent conformability to uneven shapes and excellent coverage (embedding) for recesses such as half-cut grooves. The curable compound (C) may be an oligomer component or a low molecular weight compound. In the case of a low molecular weight compound, Mw is replaced with the molecular weight.
[0031] The upper limit of Mw of the high molecular weight resin (P) is preferably 300,000, more preferably 250,000, even more preferably 200,000, and even more preferably 150,000, from the viewpoint of improving the coverage of the half-cut groove. The lower limit of Mw of the high molecular weight resin (P) is more preferably 40,000, even more preferably 60,000, and even more preferably 80,000, from the viewpoint of adjusting the elongation rate at 100° C. As Mw increases, the elongation rate at 100° C. tends to increase.
[0032] Examples of the high molecular weight resin (P) include polyurethane resin, polyurethane urea resin, phenoxy resin, acrylic resin, polyester resin, polyamide resin, polystyrene resin, polycarbonate resin, polyamideimide resin, polyesteramide resin, polyetherester resin and polyimide resin. The high molecular weight resin (P) is used alone or in combination of two or more kinds.
[0033] The high molecular weight resin (P) may be any of a thermoplastic resin, a photocurable resin, and a thermosetting resin, but preferably contains a thermosetting resin capable of crosslinking with the curable compound (C) from the viewpoint of obtaining a highly reliable SC layer. The thermosetting resin is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and even more preferably 90% by mass or more, based on 100% by mass of the high molecular weight resin (P), and may be 100% by mass.
[0034] The high molecular weight resin (P) preferably contains a thermosetting resin having a reactive functional group that reacts with the functional group of the curable compound (C) to form a crosslinked structure. Examples of such reactive functional groups include a carboxy group, a hydroxyl group, an amino group, an epoxy group, an oxetanyl group, an oxazoline group, an oxazine group, an aziridine group, a thiol group, an isocyanate group, a blocked isocyanate group, and a silanol group. Among these, the carboxy group and the hydroxyl group are preferable in terms of the storage stability of the electromagnetic wave shielding sheet.
[0035] The acid value of the high molecular weight resin (P) is preferably 3 to 30 mgKOH / g. By setting the acid value within the above range, adhesion to the wafer is improved. The acid value is more preferably 4 to 25 mgKOH / g, and further preferably 5 to 20 mgKOH / g. Suitable examples of the high molecular weight resin (P) having thermosetting properties include the above-mentioned resins having a carboxy group and / or a hydroxyl group (polyurethane resin, polyurethane urea resin, phenoxy resin, acrylic resin, polyester resin, polyamide resin, epoxy resin, polystyrene resin, polycarbonate resin, polyamideimide resin, polyesteramide resin, polyetherester resin, and polyimide resin).
[0036] From the viewpoint of achieving both the above-mentioned elongation percentage at 100° C. and Young's modulus at 100° C. after curing, the Tg of the high molecular weight resin (P) is preferably −20 to 40° C., more preferably −10 to 30° C., and even more preferably 0 to 20° C. When two or more types of high molecular weight resins (P) are used, it is preferable that the high molecular weight resin (P) that is the main component with the largest blend amount satisfies −20 to 40° C., and the main component is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 90% by mass or more relative to the high molecular weight resin (P).
[0037] The curable compound (C) with Mw of 5,000 or less plays a role in forming a crosslinked structure, increasing flexibility when covering the ES sheet, and imparting excellent conformability to uneven shapes. In addition, after curing, a highly reliable SC layer is obtained by forming a crosslinked network.
[0038] The content of the curable compound (C) is preferably 5 to 100 parts by mass relative to 100 parts by mass of the high molecular weight resin (P). The lower limit of the content of the curable compound (C) is more preferably 10 parts by mass, further preferably 12 parts by mass, further more preferably 15 parts by mass, and particularly preferably 20 parts by mass. The upper limit of the content of the curable compound (C) is more preferably 80 parts by mass, further preferably 70 parts by mass, further more preferably 60 parts by mass, and particularly preferably 50 parts by mass.
[0039] Examples of the curable compound (C) include an epoxy group-containing compound (E), an isocyanate compound, a carbodiimide group-containing compound, an aziridine compound, an acid anhydride group-containing compound, a dicyandiamide compound, an amine compound such as an aromatic diamine compound, an organometallic compound such as a metal chelate compound, a maleimide group-containing compound, and a phenolic compound such as a phenol novolac resin. Among these, it is preferable to include an epoxy group-containing compound (E) from the viewpoint of increasing the flexibility of the ES sheet when it is coated and increasing the reliability after coating. From the viewpoint of adjusting the curing speed of the semi-curing (B stage curing) and the main curing (C stage curing), it is preferable to use the epoxy group-containing compound (E) in combination with a curable compound other than the epoxy group-containing compound (E). A suitable example is a combination of an epoxy group-containing compound (E) with one or more selected from an aziridine compound, an isocyanate compound, and a maleimide group-containing compound.
[0040] In 100% by mass of the curable compound (C), the content of the epoxy group-containing compound (E) is preferably 50% by mass or more, more preferably 70% by mass, even more preferably 85% by mass, and even more preferably 90% by mass or more. The upper limit of the content may be 100% by mass.
[0041] In 100% by mass of the curable compound (C), the amount of the other curable compound used in combination with the epoxy group-containing compound (E) is preferably 50% by mass or less, more preferably 30% by mass or less, even more preferably 15% by mass or less, and even more preferably 10% by mass or less. From the viewpoint of bringing out the effect of the other curable compound used in combination, the lower limit is preferably 0.1% by mass, more preferably 0.3% by mass, and even more preferably 0.4% by mass.
[0042] In 100 parts by mass of the binder component, the total content of the high molecular weight resin (P) and the epoxy group-containing compound (E) is preferably 70 parts by mass or more, more preferably 80 parts by mass or more, and even more preferably 90 parts by mass or more, and may be 100 parts by mass.
[0043] The epoxy group-containing compound (E) is not particularly limited as long as it has an epoxy group, but from the viewpoint of adjusting the Young's modulus at 100°C of the cured sheet after treating the electromagnetic shielding sheet at 180°C for 2 hours to 100 to 1000 MPa, a bifunctional or more polyfunctional epoxy group-containing compound (E) is preferred. In a hot press or the like, the epoxy group of the epoxy group-containing compound (E) is thermally crosslinked with a carboxyl group or a hydroxyl group of the thermosetting resin to obtain a crosslinked structure. From the viewpoint of increasing the flexibility and conformability in the coating process of the ES sheet and effectively bringing out stress relaxation after coating, an epoxy group-containing compound (E) that is liquid at room temperature and normal pressure is preferred as the epoxy group-containing compound (E).
[0044] From the viewpoint of easily obtaining an SC layer having the above Young's modulus, the epoxy group equivalent of the epoxy group-containing compound (E) is preferably 110 to 1000 g / eq. The lower limit of the epoxy group equivalent is more preferably 115 g / eq, and even more preferably 150 g / eq. The upper limit of the epoxy group equivalent is more preferably 900 g / eq, more preferably 750 g / eq, even more preferably 500 g / eq, and particularly preferably 280 g / eq. From the viewpoint of more effectively increasing flexibility, the epoxy group-containing compound (E) is preferably contained in an amount of 10 to 80 parts by mass per 100 parts by mass of the high molecular weight resin (P). By using the above blending amount, the flexibility of the shielding film can be increased. By setting the epoxy equivalent of the epoxy group-containing compound (E) to 110 to 1000 g / eq, the crosslink density in the semi-cured product of the shielding film can be adjusted, and the edge coverage can be effectively increased. Here, the "edge" refers to the edge of the uneven portion, the corner, etc. The epoxy equivalent is expressed in grams of epoxy compounds containing 1 gram equivalent of epoxy groups [g / eq], and is calculated according to the method specified in JIS K 7236.
[0045] Examples of the epoxy group-containing compound (E) include glycidyl ether type epoxy compounds, glycidylamine type epoxy compounds, glycidyl ester type epoxy compounds, and cyclic aliphatic (alicyclic) epoxy compounds. Examples of the glycidyl ether type epoxy compound include bisphenol A type epoxy compounds, bisphenol F type epoxy compounds, bisphenol S type epoxy compounds, bisphenol AD type epoxy compounds, cresol novolac type epoxy compounds, phenol novolac type epoxy compounds, α-naphthol novolac type epoxy compounds, bisphenol A type novolac type epoxy compounds, dicyclopentadiene type epoxy compounds, tetrabromobisphenol A type epoxy compounds, brominated phenol novolac type epoxy compounds, tris(glycidyloxyphenyl)methane, and tetrakis(glycidyloxyphenyl)ethane. Examples of the glycidylamine type epoxy compound include tetraglycidyldiaminodiphenylmethane, triglycidyl paraaminophenol, triglycidyl meta-aminophenol, and tetraglycidyl meta-xylylenediamine. Examples of the glycidyl ester type epoxy compound include diglycidyl phthalate, diglycidyl hexahydrophthalate, and diglycidyl tetrahydrophthalate. Examples of the cyclic aliphatic (alicyclic) epoxy compound include epoxycyclohexylmethyl-epoxycyclohexanecarboxylate and bis(epoxycyclohexyl)adipate. Liquid epoxy compounds can also be used.
[0046] The epoxy group-containing compound (E) preferably has functional groups other than epoxy groups. Examples of the other functional groups include hydroxyl groups, secondary amino groups, and tertiary amino groups. By using an epoxy group-containing compound (E) having such other functional groups in addition to bifunctional or higher epoxy groups, the crosslinking density under a given curing condition can be effectively increased, and the PCT resistance can be improved. Furthermore, by having hydroxyl groups and / or amino groups, the adhesion to an adherend such as a wafer can be improved, and as a result, good PCT resistance and adhesion can be simultaneously satisfied.
[0047] The binder component may contain other components than those described above without departing from the scope of the present disclosure. For example, it may contain a tackifier resin having an Mw of less than 10,000, a thermoplastic resin, a thermosetting resin, a photocurable resin, or the like. Examples of the tackifier resin include rosin-based resins, terpene-based resins, alicyclic petroleum resins, and aromatic petroleum resins.
[0048] Examples of the conductive filler (F) include metal particles, conductive metal oxide particles, particles having a conductive polymer, and metal-coated particles. Examples of metal particles include metal powders of gold, silver, copper, palladium, aluminum, nickel, iron, titanium, manganese, zinc, tungsten, platinum, lead, tin, and the like; alloy powders of solder, steel, stainless steel, and the like; and core-shell type of silver-coated copper powder, gold-coated copper powder, silver-coated nickel powder, and gold-coated nickel powder. Excellent conductivity can be obtained by using a filler (F) containing silver. The content of silver in the silver-coated copper is preferably 6 to 20 mass% in 100 mass% of the filler (F), more preferably 8 to 17 mass%, and even more preferably 10 to 15 mass%. In the case of a core-shell type filler, the coverage rate of the coating layer with respect to the core part is preferably 60 mass% or more, more preferably 70 mass% or more, and even more preferably 80 mass% or more, on average, in 100 mass% of the entire surface. Examples of metal oxide particles include zinc oxide, indium oxide, and tin oxide, which have electrical conductivity. Examples of particles having a conductive polymer include polyacetylene particles, polythiophene particles, polyacetylene particles, polypyrrole particles, and particles having a surface coated with any of these. Examples of metal-coated particles include resin particles whose surfaces are coated with a metal such as gold or silver, and inorganic particles such as glass or ceramic particles whose surfaces are coated with a metal. Examples of the conductive carbon material include carbon black, acetylene black, ketjen black, graphite, carbon nanotubes, graphene, fullerene, carbon nanocoils, carbon microcoils, and carbon fibers.
[0049] Examples of the shape of the filler (F) include flake-shaped (scale-shaped), dendritic, fibrous, needle-shaped, and spherical fillers. The filler (F) is used alone or in a mixture. When used in combination, examples include a combination of a flake-shaped filler and a dendritic filler, a combination of a flake-shaped filler, a dendritic filler and a spherical filler, and a combination of a flake-shaped filler and a spherical filler. Of these, from the viewpoint of improving the edge coverage of the SC layer, a flake-shaped filler alone or a combination of a flake-shaped filler and a dendritic filler is more preferable.
[0050] Average particle size of flake filler D 50 The average particle diameter D of the dendritic filler (F) is preferably 0.5 to 50 μm, more preferably 1 to 30 μm, further preferably 2 to 20 μm, and particularly preferably 2 to 10 μm. 50 Similarly, the preferred range of is preferably 2 to 100 μm, more preferably 2 to 80 μm, further preferably 3 to 50 μm, and particularly preferably 5 to 20 μm.
[0051] The specific surface area of the flake filler is 0.2 to 4.0 m 2 / g is preferable, and 0.4 to 3.5m 2 / g is more preferable. Further, 0.5 to 3.0m 2 / g, and particularly preferably 1.0 to 2.5 m 2 / g. The average particle size of the dendritic filler, D 50 The preferred range of is also 0.2 to 2.0 m. 2 / g is preferable, and 0.3 to 1.8 μm is more preferable. Further, 0.4 to 1.6 μm is even more preferable. 2 / g, and particularly preferably 0.5 to 1.5 m 2 / g.
[0052] From the viewpoint of obtaining excellent electromagnetic shielding properties, the content of the filler (F) is preferably 45 to 85 mass% relative to 100 mass% of the sheet. The lower limit is more preferably 50 mass%, and even more preferably 55 mass%. The upper limit is more preferably 82 mass%, and even more preferably 80 mass%.
[0053] Average specific surface area of filler (F) [m 2 The product of the amount of the filler (F) per 100 parts by mass of the binder component [g] and the amount of the filler (F) per 100 parts by mass of the binder component [g] is 50 to 1200 m 2 is preferable, and 100 to 1000 m 2 More preferably, the range is 200 to 800 m. 2 and particularly preferably 300 to 600 m 2 It is.
[0054] The shielding film may contain an electromagnetic wave absorbing filler in addition to the conductive filler (F). Examples of the electromagnetic wave absorbing filler include dielectric loss electromagnetic wave absorbing materials such as carbon particles, and magnetic loss electromagnetic wave absorbing materials such as ferrite and soft magnetic metal powder.
[0055] Examples of the electromagnetic wave absorbing filler include iron alloys such as iron, Fe-Ni alloy, Fe-Co alloy, Fe-Cr alloy, Fe-Si alloy, Fe-Al alloy, Fe-Cr-Si alloy, Fe-Cr-Al alloy, and Fe-Si-Al alloy, ferrite-based substances such as Mg-Zn ferrite, Mn-Zn ferrite, Mn-Mg ferrite, Cu-Zn ferrite, Mg-Mn-Sr ferrite, and Ni-Zn ferrite, and carbon fillers. Examples of the carbon filler include acetylene black, ketjen black, furnace black, carbon black, carbon fiber, fillers made of carbon nanotubes, graphene fillers, graphite fillers, and carbon nanowalls.
[0056] This ES sheet is particularly suitable for use in covering wafers with half-cut grooves. In addition, this ES sheet can be applied to any application where it is desired to provide electromagnetic shielding properties by attaching it to an adherend. It can also provide shielding effects on the sides of semiconductor devices. In addition, because it can be covered in one go, it offers greater design freedom and is highly versatile.
[0057] The elongation percentage of the ES sheet at 100°C can be adjusted by the type, molecular weight, content, and functional group of the binder component of the sheet. For example, it can be adjusted by adjusting the blending amount of the high molecular weight resin (P) and the epoxy group-containing compound (E). The elongation percentage tends to increase by increasing the Mw of the high molecular weight resin (P). Also, the elongation percentage tends to increase by decreasing the Tg of the high molecular weight resin (P). The elongation percentage of the ES sheet at 100°C can be adjusted by setting the epoxy group equivalent of the epoxy group-containing compound (E) within the above-mentioned range. Also, the elongation percentage can be adjusted by the combination of the high molecular weight resin (P) and the epoxy group-containing compound (E).
[0058] The Young's modulus at 100° C. of the cured sheet after treating the ES sheet at 180° C. for 2 hours tends to increase with an increase in the amount of filler. The Young's modulus also tends to increase with an increase in the Tg or acid value of the high molecular weight resin (P).
[0059] Alternatively or in combination with the above method, the Young's modulus at 100°C of the cured sheet after treatment of the ES sheet at 180°C for 2 hours can be controlled to 100 to 1000 MPa by controlling the type and amount of filler (F). 50 Changing the BET specific surface area, tap density, and surface treatment are also effective in controlling the Young's modulus.
[0060] The ES sheet is thermally bonded to the entire main surface of a silicon bare wafer at 120°C and 5 MPa for 3 minutes, and then treated at 180°C for 2 hours. In the SC layer derived from the ES sheet, the peeling rate in the adhesion test after a pressure cooker test based on JIS K5600-5-6 is adjusted to less than 15% by adjusting the type and amount of the high molecular weight resin (P) and the epoxy group-containing compound (E). As the Mw of the high molecular weight resin (P) increases, the internal cohesive force of the sheet increases, so the peeling rate tends to decrease. In addition, as the acid value of the high molecular weight resin (P) increases, the interaction at the interface of the adherend such as a wafer increases, so the peeling rate tends to decrease. In addition, the adhesion force can be adjusted by adjusting the acid value and Mw of the high molecular weight resin (P) and the epoxy equivalent of the epoxy group-containing compound (E).
[0061] The shielding film may contain organic fillers and inorganic fillers other than the filler (F) and various additives without departing from the spirit of the present disclosure. Specifically, the shielding film may contain monomers, oligomers, curing accelerators, curing retarders, silane coupling agents, colorants, flame retardants, antistatic agents, antioxidants, softeners, surface conditioners, lubricants, antiblocking agents, adhesion improvers, etc.
[0062] 2-2.Non-shielding film The non-shielding film contains at least a binder component. The non-shielding film may contain an organic filler and / or an inorganic filler. By composite the binder component with an organic filler or an inorganic filler, the properties of the binder component can be improved. For example, mechanical properties, thermal properties, processability, flame retardancy, transparency, refraction, heat dissipation, dispersibility, etc. can be imparted.
[0063] Examples of inorganic fillers include inorganic compounds such as silica, alumina, titanium oxide, zinc oxide, antimony trioxide, magnesium oxide, tin oxide, zirconium oxide, magnesium hydroxide, barium sulfate, calcium carbonate, talc, kaolinite, mica, sericite, montmorolinite, kaolinite, bentonite, basic magnesium carbonate, boron nitride, aluminum nitride, and titanium nitride.
[0064] Suitable examples of the binder component include the same resins as those used in the shielding film. The filler can be appropriately selected depending on the function of the non-shielding film. For example, when it is desired to impart thermal conductivity to a non-shielding film, examples of the inorganic materials that can be used include, in addition to conductive fillers, nitrides such as boron nitride, aluminum nitride, and gallium nitride; metal oxides such as aluminum oxide, silicon oxide (silicon dioxide), titanium oxide, zirconium oxide, zinc oxide, tin oxide, copper oxide, and nickel oxide; metal hydroxides and hydrated metal compounds such as aluminum hydroxide, boehmite, magnesium hydroxide, calcium hydroxide, zinc hydroxide, silicic acid, iron hydroxide, copper hydroxide, barium hydroxide, zirconium oxide hydrate, tin oxide hydrate, basic magnesium carbonate, hydrotalcite, dawsonite, borax, and zinc borate; carbides such as silicon carbide, boron carbide, nitrogen carbide, and calcium carbide; carbonates such as calcium carbonate; titanates such as barium titanate and potassium titanate; carbon-based materials such as carbon black, carbon tubes (carbon nanotubes), carbon fibers, and diamond; and glass.
[0065] 2-3. Manufacturing method of electromagnetic wave shielding sheet The manufacturing method of the present ES sheet will be described below, however, the manufacturing method of the present ES sheet is not limited to the following method.
[0066] First, a resin composition for obtaining the film constituting the present ES sheet is prepared. The resin composition for obtaining the shielding film is obtained by mixing the filler (F), the binder component, the solvent, etc. The mixing method is not limited as long as it can be mixed uniformly. The resin composition for obtaining the non-shielding film such as the protective film is obtained by mixing the binder component, the solvent, etc.
[0067] In order to improve the uniform dispersion of the filler, a mixing device may be used. For example, a stirring device equipped with a blade (Henschel mixer, pressure kneader, Banbury mixer, planetary mixer, etc.), a grinding device equipped with a media (ball mill, attritor, basket mill, sand mill, sand grinder, Dyno Mill, Dispermat, SC Mill, spike mill or agitator mill, etc.), a dispersing device equipped with other mechanisms (microfluidizer, nanomizer, ultimaizer, ultrasonic homogenizer, dissolver, disper, high-speed impeller, rotation and revolution stirrer, colloid mill, thin film swirl type high-speed mixer, etc.) can be exemplified. Also, mixing may be performed while degassing.
[0068] The viscosity of the resin composition may be appropriately set according to the desired thickness of the film. The shielding film is obtained by coating the prepared resin composition on a releasable substrate and drying by heating. Similarly, the non-shielding film is obtained by coating the prepared resin composition on a releasable substrate and drying by heating. Examples of the coating method of the resin composition include gravure coating, kiss coating, die coating, lip coating, comma coating, blade coating, roll coating, knife coating, spray coating, bar coating, spin coating, and dip coating.
[0069] When the ES sheet is composed of only a shielding film, the ES sheet is obtained by peeling the film from a releasable substrate. When the ES sheet has a laminated structure of a shielding film / non-shielding film, each film may be laminated to bond them to each other. A laminate may be obtained by applying a resin composition for forming a non-shielding film onto a shielding film formed on a releasable substrate and drying by heating. A laminate may be obtained by applying a resin composition for forming a shielding film onto a non-shielding film formed on a releasable substrate and drying by heating. The non-shielding film is, for example, a protective film.
[0070] 3. Semiconductor device and manufacturing method thereof 9 shows a schematic cross-sectional view of an example of a main part of a semiconductor device obtained by singulating a shield processed wafer. In the semiconductor device 201, the shield processed wafer is singulated in element formation region units, and an SC layer 2 obtained by heating and hardening an ES sheet covers from the element formation region 12 to the half-cut groove 11. The SC layer 2 may be heat-cured before singulation, or may be heat-cured after singulation.
[0071] Fig. 10 shows a schematic cross-sectional view of an example of a semiconductor device according to a modified example. In the example of Fig. 9, the SC layer 2 is coated along the sidewall and bottom of the half-cut groove, but as shown in Fig. 10, the SC layer 2 may be filled in the entire half-cut groove. When the width of the half-cut groove is narrow, it is effective to fill the half-cut groove with the SC layer 2 and separate the wafer and the SC layer 2 along the scribe line by dicing.
[0072] An example of the method for manufacturing the semiconductor device according to the present disclosure will be described below, although the method for manufacturing the semiconductor device according to the present disclosure is not limited to the method described below.
[0073] First, in order to form a circuit pattern on the bare wafer, the bare wafer is subjected to high-temperature treatment to form an oxide film on the bare wafer surface. Next, a photosensitive photoresist, an insulating layer, a wiring pattern, etc. are formed to form the semiconductor element forming wafer 1, and then a multilayer wiring structure portion 14, etc. are formed (see FIG. 11). Next, a surface protection film is formed as necessary. After that, half-cut grooves 11 are formed from the surface of the semiconductor element forming wafer 1 to halfway through the wafer along the scribe lines 17 (see FIG. 1) (see FIG. 12). The half-cut grooves can be formed by mechanical cutting using a rotating blade or the like, or by laser grooving.
[0074] As a specific example, the wafer is fixed in a vacuum chuck of a dicing device while being vacuum-adsorbed, and then dicing is performed from the front side of the wafer with a dicing blade along the scribe lines in the X direction and the Y direction to form half-cut grooves 11 that reach the inside of the wafer.
[0075] Next, the ES sheet 3 is placed on the semiconductor element forming wafer 1 in which the half-cut grooves 11 are formed. In order to improve the coverage of the half-cut grooves 11 with the ES sheet 3, it is preferable to place a cushion sheet 33 on the ES sheet 3 as shown in Fig. 13. Furthermore, a reinforcing sheet 34 may be laminated on the upper layer of the cushion sheet 33 as necessary.
[0076] The provision of the cushion sheet 33 improves the ability of the ES sheet 3 to conform to the half-cut grooves 11. The cushion material is a layer that melts during heat pressing, and is made of a material that has releasability. The reinforcing sheet transmits the pressing force to the cushion sheet, improving the ability of the ES sheet to be embedded into the stepped parts of the adherend.
[0077] The semiconductor element forming wafer 1 is fixed to a vacuum suction stage 50 (see FIG. 14), and the laminate of the ES sheet 3 / cushion sheet 33 / reinforcement sheet 34 is thermocompression bonded. Prior to thermocompression bonding, the ES sheet 3 may be temporarily attached to the upper surface of the semiconductor element forming wafer 1. The temporary attachment method is, for example, to lightly heat press the ES sheet 3 onto the entire surface or edge of the semiconductor element forming wafer 1 with a heat source.
[0078] The reinforcing sheet 34 can be appropriately selected from resin films, metal plates, etc. For example, polyethylene terephthalate, polyethylene naphthalate, polyvinyl fluoride, polyvinylidene fluoride, hard polyvinyl chloride, polyvinylidene chloride, nylon, polyimide, polystyrene, polyvinyl alcohol, ethylene-vinyl alcohol copolymer, polycarbonate, polyacrylonitrile, polybutene, soft polyvinyl chloride, polyvinylidene fluoride, polyethylene, polypropylene, polyurethane resin, ethylene-vinyl acetate copolymer, polyvinyl acetate, and other plastic sheets, glassine paper, wood-free paper, craft paper, coated paper, and other papers, various nonwoven fabrics, synthetic paper, metal foils, and composite films combining these, etc. are listed. Among these, from the viewpoint of handling and cost, any of polyethylene terephthalate, polyester, polycarbonate, polyimide, and polyphenylene sulfide is preferable. Furthermore, polyethylene terephthalate and polyimide are more preferable.
[0079] In order to facilitate peeling from the SC layer after heat pressing, it is preferable that the cushion layer 33' obtained from the cushion sheet 33 has a release layer formed on the bonding surface with the ES sheet. Examples of such a release layer include polypropylene, polymethylpentene, cyclic olefin polymer, silicone, and fluororesin.
[0080] Commercially available cushion layers include "CR1012", "CR1012MT4", "CR1031", "CR1033", "CR1040", and "CR2031MT4" manufactured by Mitsui Tocello Co., Ltd. These commercially available cushion layers often have a layered structure in which both sides of the cushion layer are sandwiched between polymethylpentene as release layers. In this specification, the integrated structure including the release layer is called a cushion sheet. By laminating a reinforcing sheet on one side of this, it is possible to improve embedding properties and substrate cracking.
[0081] The thickness of the cushion sheet is preferably 50 to 300 μm, more preferably 75 to 250 μm, and even more preferably 100 to 200 μm. By making it 50 μm or more, embeddability can be improved. By making it 300 μm or less, the handleability of the ES sheet can be improved. Note that the thickness of the cushion layer includes the release layer, if any.
[0082] The thickness of the reinforcing sheet 34 is preferably 20 μm or more, more preferably 25 μm or more, and even more preferably 38 μm or more. By making the thickness of the reinforcing sheet 34 20 μm or more, the strength of the reinforcing sheet is improved, so that embeddability, releasability, and handleability are further improved. The thickness of the reinforcing sheet is not particularly limited, but is preferably 250 μm or less, because the releasability and handleability of the ES sheet are improved.
[0083] The ES sheet 3 is thermocompression bonded to the wafer to form an SC layer 2 on the semiconductor element forming wafer 1. A press substrate 40 is lowered from above the reinforcing sheet 34 to perform a heat press (see FIG. 15). The ES sheet 3 is stretched to fit the half-cut grooves provided in the wafer by the pressure caused by the melting of the cushion sheet 33, and covers the multilayer wiring structure 14 and the half-cut grooves 11 in conformity with each other, forming the SC layer 2 (see FIG. 15).
[0084] The temperature in the heat press step is preferably equal to or higher than the melting temperature of the cushion sheet 33 and lower than the melting temperature of the reinforcing sheet 34. By setting the temperature in the above-mentioned range, the strength of the reinforcing sheet can be maintained while melting the cushion sheet. The heating temperature in the heat press step is preferably 100°C or higher, more preferably 110°C or higher, and even more preferably 120°C or higher. The upper limit depends on the heat resistance of the multilayer wiring structure 14, but is preferably 220°C or lower, more preferably 200°C or lower, and even more preferably 180°C or lower.
[0085] The pressure in the heat press step is appropriately set according to the thickness of the wafer so as not to crack the wafer. For example, it is about 1 to 15 MPa. More preferably, it is 1.5 to 10 MPa, and further preferably, it is 2 to 5 MPa. The heat press time is, for example, about 1 minute to 2 hours. The curing process may be completed in the heat press step, or a separate process of curing the wafer after the heat press may be provided. Note that the thermosetting resin in the binder component may be partially cured or substantially cured before the heat press as long as it is capable of flowing. The heat press device may be a pressure type heat press device, a transfer mold device, a compression mold device, a vacuum / pressure molding device, or the like.
[0086] Thereafter, the press substrate 40 is released, and the cushion layer 33' and the reinforcing sheet 34 are removed. Through these steps, a wafer with a shield is obtained as shown in Fig. 2. The top surface may be removed by etching as shown in Fig. 5.
[0087] In the above embodiment, the ES sheet 3, the cushion sheet 33, and the reinforcing sheet 34 are overlapped and used, but a laminate in which they are bonded in any combination may be used. For example, a laminate in which an ES sheet / cushion sheet / reinforcing sheet, an ES sheet / cushion sheet, or a cushion sheet / reinforcing sheet are bonded together may be used. By bonding the reinforcing sheet and the cushion sheet, the peelability can be significantly improved.
[0088] Next, a singulation process is performed along the scribe lines. Specifically, the shield processed wafer is singulated. The singulation method can be performed by mechanical cutting such as a rotary blade or laser grooving, similar to the half-cut groove. Alternatively, the wafer may be cut by polishing the back side of the wafer to thin the wafer to the half-cut groove. EXAMPLES
[0089] The present disclosure will be described in more detail below with reference to examples, but the scope of the present disclosure is not limited thereto. In the examples, "parts" and "%" represent "parts by mass" and "% by mass".
[0090] (a)Measurement method The values obtained in this example were obtained by the following method. (i) Weight average molecular weight (Mw) The Mw was measured using a Tosoh GPC (gel permeation chromatography) "HPC-8020." GPC is a liquid chromatography that separates and quantifies substances dissolved in a solvent (THF; tetrahydrofuran) based on the difference in their molecular size. The measurement was performed using two "LF-604" columns (Showa Denko: GPC column for rapid analysis: 6 mm ID x 150 mm size) connected in series at a flow rate of 0.6 mL / min and a column temperature of 40°C, and the weight average molecular weight (Mw) was determined in polystyrene equivalent.
[0091] (ii) Acid value of resin Approximately 1 g of resin was precisely weighed and placed in a stoppered Erlenmeyer flask, and 50 mL of a toluene / ethanol (volume ratio: toluene / ethanol = 2 / 1) mixture was added to dissolve. Phenolphthalein test solution was added as an indicator and the solution was held for 30 seconds. After that, titration was performed with 0.1 mol / L alcoholic potassium hydroxide solution until the solution turned a pale pink color. The acid value was calculated using the following formula. The acid value was the value for the resin in its dry state. Acid value (mgKOH / g)=(a×F×56.1×0.1) / S S: Amount of sample taken × (solid content of sample / 100) (g) a: Titration volume (mL) of 0.1 mol / L alcoholic potassium hydroxide solution F: Potency of 0.1 mol / L alcoholic potassium hydroxide solution
[0092] (iii) Tg of resin Tg was measured using a dynamic viscoelasticity measuring device DVA-200 (manufactured by IT Measurement & Control Co., Ltd.) in accordance with JIS K7198. A 50 μm thick PET film coated with a silicone release agent was prepared as a release substrate. The resin was applied to this release substrate using a doctor blade to a thickness of 20 μm, and the sheet obtained by drying at 100 ° C for 2 minutes was cut into 0.5 cm × 3 cm, and the release film was peeled off and used for measurement. The measurement was performed in a tensile deformation mode, and the temperature at which the main dispersion peak of the loss tangent (tan δ) appeared was determined as Tg, measured at a strain of 0.08%, a frequency of 10 Hz, and a heating rate of 10 ° C / min.
[0093] (iv) Preparation of half-cut wafers for testing A bare silicon wafer (size 100 mmφ, thickness 525 μm) was prepared, and a dicing device (DISCO, DAD323) was used to form half-cut grooves with a 4000 μm lattice angle, a width of 200 μm, and a depth of 200 μm to obtain a half-cut wafer for testing.
[0094] (b) Production of resin composition, electromagnetic wave shielding sheet, and laminate [Production of resin composition of Example 1] A resin composition was obtained by adding 100 parts of the solid content of high molecular weight resin P3, 40 parts of epoxy group-containing compound E3, 1 part of curable compound C1, 180 parts of filler F2, and 35 parts of filler F4 to a container, adding a mixed solvent of toluene:isopropyl alcohol (mass ratio 2:1) so that the non-volatile content (solid content) concentration was 35%, and stirring with a disper for 10 minutes. The solid content equivalent amount of each component is shown in Table 1.
[0095] [Examples 2 to 20 and Comparative Examples 1 to 6] Resin compositions were produced in the same manner as in Example 1 except for the changes shown in Tables 1 to 3.
[0096] The materials used in the examples and their abbreviations in Tables 1 to 3 are shown below. <Binder components> [High molecular weight resin (P)] P1: Polycarbonate resin, Mw=180,000, acid value 10 [mgKOH / g], Tg10℃ (manufactured by Toyochem Co., Ltd.) P2: Polycarbonate resin, Mw=260,000, acid value 10 [mgKOH / g], Tg10℃ (manufactured by Toyochem Co., Ltd.) P3: Polycarbonate resin, Mw=120,000, acid value 10 [mgKOH / g], Tg10℃ (manufactured by Toyochem Co., Ltd.) P4: Polycarbonate resin, Mw=110,000, acid value 12 [mgKOH / g], Tg-10℃ (manufactured by Toyochem Co., Ltd.) P5: Polycarbonate resin, Mw=50,000, acid value 18 [mgKOH / g], Tg20℃ (manufactured by Toyochem Co., Ltd.) P6: Polycarbonate resin, Mw=110,000, acid value 3 [mgKOH / g], Tg10℃ (manufactured by Toyochem Co., Ltd.) P7: Polycarbonate resin, Mw=110,000, acid value 28 [mgKOH / g], Tg10℃ (manufactured by Toyochem Co., Ltd.) P8: Urethane resin, Mw=130,000, acid value 10 [mgKOH / g], Tg40℃ (manufactured by Toyochem Co., Ltd.) P9: Urethane resin, Mw=130,000, acid value 10 [mgKOH / g], Tg60℃ (manufactured by Toyochem Co., Ltd.) P10: Ester resin, Mw=140,000, acid value 10 [mgKOH / g], Tg-15℃ (manufactured by Toyochem Co., Ltd.) [Other resins] R1: Acrylic resin, Mw=8,000, acid value 15 [mgKOH / g] (manufactured by Toyochem Co., Ltd.) <Curable compound (C)> C1: "Chemithite PZ-33" (aziridine compound, Mw=425) manufactured by Nippon Shokubai Co., Ltd. [Epoxy group-containing compound (E)] E1: "jER604" (diaminodiphenylmethane type epoxy resin, Mw=350, epoxy equivalent=120g / eq) manufactured by Mitsubishi Chemical Corporation E2: "jER1032H" (trisphenolmethane type epoxy resin, Mw=500, epoxy equivalent=170g / eq) manufactured by Mitsubishi Chemical Corporation E3: "jER834" (Bisphenol A type epoxy resin, Mw=470, epoxy equivalent=250g / eq) manufactured by Mitsubishi Chemical Corporation E4: "EPICLON1050" (bisphenol A type epoxy resin, Mw=900, epoxy equivalent=475g / eq) manufactured by DIC Corporation E5: "EPICLON3050" (bisphenol A type epoxy resin, Mw=1800, epoxy equivalent=800g / eq) manufactured by DIC Corporation [Other curable compounds] R2: "jER1010" (bisphenol A type epoxy resin, Mw=5500, epoxy equivalent=4000g / eq) manufactured by Mitsubishi Chemical Corporation <Conductive filler (F)> F1: Flake-like silver filler (D 50 =1.0~3.0μm, average specific surface area 1.1m 2 / g) Tokusen Kogyo Co., Ltd. F2: Flake-like silver filler (D 50 =4.0~7.0μm, average specific surface area 1.5m 2 / g) Manufactured by Fukuda Metal Industry Co., Ltd. F3: Flake-like silver filler (D 50 =5.0~10.0μm, average specific surface area 0.3m 2 / g) Manufactured by Fukuda Metal Industry Co., Ltd. F4: Dendritic silver-coated copper filler (D 50 =7.4μm, average specific surface area 0.7m 2 / g) Mitsui Mining & Smelting Co., Ltd. F5: Dendritic silver-coated copper filler (scale silver filler D 50 =10.4μm, average specific surface area 0.6m 2 / g) Made by DOWA
[0097] [Table 1]
[0098] [Table 2]
[0099] [Table 3]
[0100] (Manufacture of electromagnetic shielding sheets) A 50 μm-thick PET film with a silicone release agent coated on its surface was prepared as a releasable substrate. The resin composition of each Example and Comparative Example was applied onto this releasable substrate using a doctor blade so that the dry thickness was 40 μm. Then, the composition was dried at 100° C. for 2 minutes to obtain an electromagnetic wave shielding sheet with a releasable substrate according to each Example and Comparative Example.
[0101] (Preparation of Laminate) Thereafter, a releasable cushion member was prepared, and the sheet surface of the electromagnetic wave shielding sheet with releasable substrate of each Example and Comparative Example was laminated to a cushion sheet (CR1040 manufactured by Mitsui Tocello Co., Ltd.) using a thermal laminator at a temperature of 70°C, a pressure of 0.1 MPa, and a speed of 1 m / min to obtain a laminate according to each Example and Comparative Example.
[0102] (c) Characteristics of electromagnetic shielding sheets, etc. The elongation percentage and Young's modulus of the above-mentioned Examples and Comparative Examples were determined by the following methods. The results are shown in Tables 1 to 3. <Elongation at 100℃> The electromagnetic shielding sheet from which the release substrate and cushion sheet of each example had been peeled off was left to stand for 24 hours in a thermostatic chamber at 23° C. and a relative humidity of 50%, and then left to stand for 1 minute in a chamber maintained at 100° C. Thereafter, at a temperature of 100° C., the stress-strain curve of the electromagnetic shielding sheet was measured using a tensile tester "EZ Tester" (manufactured by Shimadzu Corporation) at a tensile speed of 50 mm / min and a gauge distance of 25 mm, and the elongation at the breaking point was measured and recorded as the elongation at 100° C.
[0103] <Young's modulus of cured sheet at 100℃> The electromagnetic wave shielding sheet with the release substrate and the cushion sheet peeled off was heated at 180°C for 2 hours to obtain a cured sheet. After standing in a thermo-hygrostat chamber at 23°C and 50% relative humidity, it was then left standing in a chamber maintained at 100°C for 1 minute. Thereafter, under a temperature of 100°C, the stress-strain curve of the cured sheet was measured by a tensile testing machine "EZ Tester" (manufactured by Shimadzu Corporation) under the conditions of a tensile speed of 50 mm / min and a gauge length of 25 mm. The linear regression (slope) in the region where the strain (elongation) was 0.1 to 0.3% was measured and taken as the Young's modulus at 100°C.
[0104] (d) Evaluation of electromagnetic wave shielding sheets, etc. For the above Examples and Comparative Examples, the adhesion, coating property, warp, and appearance were evaluated by the following methods. The results are shown in Table 4. <Adhesion of silicon to the bare wafer after PCT test> A silicon bare wafer (size 100 mmφ, thickness 525 μm) was prepared. The above laminate was cut into 50 mm × 50 mm, the release substrate was peeled off, and the electromagnetic wave shielding sheet layer was placed on the bare wafer. Thereafter, heat pressing was performed on the bare wafer from above the cushion sheet of the laminate under the conditions of a temperature of 120°C and a pressure of 5 MPa for 3 minutes. After heat pressing, it was cooled and the cushion layer was peeled off, and a test piece in which a shield cover layer was formed by heating at 180°C for 2 hours was obtained. Next, a pressure cooker test (conditions: 130°C, 85% RH, 0.12 MPa, 96 hours) was performed on this test substrate. Thereafter, 100 square grids with an interval of 1 mm were formed on the shield cover layer of the test substrate using a cross-cut guide according to JIS K5400. Thereafter, an adhesive tape was strongly pressure-bonded to the grid portions, and the end of the tape was quickly peeled off at an angle of 45°, and the state of the grid was evaluated according to the following criteria. +++: Peel rate less than 5%. ++: The coating film is partially peeled off along the cut line, and the peel rate is 5% or more and less than 10%. +: The coating film is partially peeled off along the cut line, and the peel rate is 10% or more and less than 15%. NG: The coating has peeled off partially or entirely along the cut line, and the peeling rate is 15% or more. Not suitable for practical use.
[0105] <Resistance between half-cut grooves> The laminate was cut to 100 mmφ, the release substrate was peeled off, and the electromagnetic shielding sheet layer was placed on the test half-cut wafer. Then, the laminate was heat-pressed from above the cushion sheet to the test half-cut wafer at a temperature of 120°C and a pressure of 5MPa for 3 minutes. After the heat press, the laminate was cooled, the cushion layer was peeled off, and the wafer was heated at 180°C for 2 hours to obtain a shielded wafer. Then, using HIOKI RM3544 and a pin-type lead probe, the probe was applied to the center of the top surface of the shield cover layer in two adjacent semiconductor element formation regions to evaluate the resistance value between the half-cut grooves. The evaluation criteria are as follows. +++: Resistance is less than 50mΩ. This is a very good result. ++: Resistance value is 50mΩ or more and less than 150mΩ. Good result. +: Resistance is 150mΩ or more and less than 300mΩ. No problem in practical use. NG: Resistance value is 300mΩ or more. Not suitable for practical use.
[0106] <Warp height> The shielded wafer obtained above was placed on a horizontal surface, and the maximum distance between the surface on which the wafer was placed and the edge of the wafer was measured to evaluate the warpage height. The evaluation criteria were as follows: +++: Warpage height is less than 1 mm. Very good result. ++: The warpage height is 1 mm or more and less than 2 mm. This is a good result. +: The warpage height is 2 mm or more and less than 5 mm. There is no problem in practical use. NG: Warpage height is 5mm or more. Not practical.
[0107] <Appearance of individual product> The top surface of the shielded wafer obtained above was fully cut with a width of 50 μm using a dicing device (DISCO DAD323) so as to pass through the center of the half-cut groove, obtaining 100 individual pieces. The appearance was then visually observed, and the number of individual pieces with peeled or chipped electromagnetic wave shielding sheets was counted. The evaluation criteria were as follows. +++: The number of individual pieces with peeled or chipped electromagnetic shielding sheets is less than 5. Very good. ++: The number of individual pieces with peeled or chipped electromagnetic shielding sheets is between 5 and 10. Good. +: The number of individual pieces with peeled or chipped electromagnetic shielding sheets was between 10 and 20. No practical problems. NG: The number of individual pieces with peeled or chipped electromagnetic shielding sheets is 20 or more. Not suitable for practical use.
[0108] [Table 4]
[0109] In the case of an electromagnetic shielding sheet having a Young's modulus of more than 1000 MPa at 100°C in the cured sheet, the resistance between the half-cut grooves was confirmed to be high, as shown in Comparative Examples 2 and 4, and there was a problem with the coverage of the recesses. In the case of a cured sheet having a Young's modulus of less than 100 MPa at 100°C, the peelability after the PCT test was confirmed to be poor, as shown in Comparative Examples 1 and 3, and there was a problem with the adhesion to the adherend. Even if the Young's modulus of the cured sheet at 100°C is less than 1000 MPa, the peelability after the PCT test is good if the elongation rate at 100°C is high, but as shown in Comparative Example 5, the resistance between the half-cut grooves was confirmed to be high, and there was a problem with the coverage of the recesses. In contrast, by using an electromagnetic shielding sheet having an elongation rate at 100°C of 100 to 1500%, and a cured sheet having a Young's modulus of 100 to 1000 MPa at 100°C after treating the electromagnetic shielding sheet at 180°C for 2 hours, it was confirmed that the sheet had excellent adhesion, coverage, warping, and appearance, as shown in Examples 1 to 28. [Explanation of symbols]
[0110] 1. Semiconductor device forming wafer 2 Shielding cover layer 3. Electromagnetic wave shielding sheet 11 Half cut groove 12 Device formation area 13 Notches 14 Multilayer wiring high-rise section 15a First insulating film 15b Second insulating film 15c Third insulating film 16 Wiring 17 Scribe Line 20 Shielding Layer 21 Non-shielded layer 30 Shielding film 31 Non-shielding film 33 Cushion Seat 34 Reinforcement sheet 40 Press Board 50 Vacuum suction stage 101 Shield processed wafer 201 Semiconductor device
Claims
1. An electromagnetic wave shielding sheet for collectively covering at least one of the main surfaces of a semiconductor wafer before being singulated, the semiconductor wafer having half-cut grooves formed in a lattice pattern and element formation regions partitioned by the half-cut grooves and arranged in a matrix pattern, the sheet comprising: The electromagnetic wave shielding sheet has at least a shielding film containing a binder component and a conductive filler (F), The electromagnetic wave shielding sheet has an elongation rate of 100 to 1500% at 100°C, The electromagnetic wave shielding sheet, wherein the cured sheet obtained by treating the electromagnetic wave shielding sheet at 180° C. for 2 hours has a Young's modulus at 100° C. of 100 to 1000 MPa.
2. The electromagnetic wave shielding sheet according to claim 1, wherein the electromagnetic wave shielding sheet is thermocompression-bonded to the entire main surface of a silicon bare wafer at 120°C and 5 MPa for 3 minutes, and then treated at 180°C for 2 hours, and then a shield cover layer derived from the electromagnetic wave shielding sheet is subjected to a pressure cooker test based on JIS K5600-5-6, and then the peeling rate in an adhesion test is less than 15%.
3. 2. The electromagnetic wave shielding sheet according to claim 1, wherein the binder component comprises a curable compound (C) having a weight-average molecular weight of 5,000 or less and a high molecular weight resin (P) having a weight-average molecular weight of 10,000 or more.
4. 2. The electromagnetic shielding sheet according to claim 1, wherein the content of the conductive filler (F) is 45 to 85 mass %.
5. Average specific surface area [m 2 / g] and the content [g] of the conductive filler (F) relative to 100 parts by mass of the binder component is 50 to 1200 [m 2 2. The electromagnetic wave shielding sheet according to claim 1, wherein
6. The curable compound (C) contains an epoxy group-containing compound (E) having a weight average molecular weight of 5,000 or less, The epoxy equivalent of the epoxy group-containing compound (E) is 110 to 1000 g / eq.
2. The electromagnetic wave shielding sheet according to claim 1, comprising 10 to 80 parts by mass of the epoxy group-containing compound (E) relative to 100 parts by mass of the high molecular weight resin (P).
7. The electromagnetic wave shielding sheet according to claim 1, wherein the electromagnetic wave shielding sheet is thermocompression-bonded to the entire main surface of a 12-inch silicon bare wafer in which half-cut grooves having a width of 200 μm and a depth of 200 μm are formed in a lattice pattern at intervals of 4000 μm, at 120° C. and 5 MPa for 3 minutes, and then treated at 180° C. for 2 hours to form a shield cover layer derived from the electromagnetic wave shielding sheet, and the resistance value between the shield cover layers covering adjacent convex portions via the half-cut grooves is 5 to 300 mΩ.
8. A shielded wafer having a shield cover layer formed of the electromagnetic wave shielding sheet according to any one of claims 1 to 7 on at least one main surface of a semiconductor wafer before being singulated.
9. 9. A semiconductor device obtained by dividing the shield processed wafer according to claim 8 into individual devices on an element forming region basis.
10. forming half-cut grooves in a semiconductor wafer before being singulated, the semiconductor wafer having element formation regions formed in a matrix along scribe lines; A step of disposing the electromagnetic wave shielding sheet according to any one of claims 1 to 7 above the semiconductor wafer; a step of thermocompression bonding the electromagnetic wave shielding sheet to the semiconductor wafer; a step of obtaining a shielding cover layer by heating and curing the electromagnetic wave shielding sheet; and dividing the semiconductor device into individual element formation region units.
Citation Information
Patent Citations
Semiconductor element, semiconductor device, and method for producing semiconductor element
JP2003347441A
Semiconductor device and method of manufacturing the same
JP2011129779A
Film for back face of flip-chip type semiconductor, film for back face of dicing tape-integrated semiconductor, and production method of film for back face of flip-chip type semiconductor
JP2016056370A
Electromagnetic wave-shielding support base-attached sealing material, sealed semiconductor element-mounted substrate, sealed semiconductor element-formed wafer, and semiconductor device
JP2016092275A
Method for manufacturing electronic component module
JP2017045931A
Cited By
Encapsulating laminated sheet, resin-encapsulated semiconductor element substrate, and resin-encapsulated semiconductor device
JP7810306B1